বিনয় সরকারের বৈঠকে : বিংশ শতাব্দীর বঙ্গ-সংস্কৃতি, দ্বিতীয় ভাগ - মুখোপাধ্যায়, হরিদাস (কলকাতা : দে'জ পাবলিশিং, 2003)
Author's interviews with Benoy Kumar Sarkar, 1887-1949, Indic scholar and educationist, on various Indian social topics.
In Bengali.
নির্ঘণ্ট অন্তর্ভুক্ত।
Microfiche.
Donated By Akbar Ali Khan
Keywords: Sarkar, Benoy Kumar, -- 1887-1949.; India -- Social conditions -- 1919-1947.; India -- Politics and government -- 1919-1947.